A prospective comparative study to evaluate the efficacy and safety of mifepristone with misoprostol over misoprostol alone in induction of labour - Mandade, Krishna; Bangal, V. B. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The clinical requirement for induction of labour arises from circumstances in which it is predicted that the outcome of the pregnancy will be better if it is artificially interrupted rather than being left to follow its natural course. The combination of Mifepristone and Misoprostol is now an established and highly effective and safe method for second and third trimester termination of pregnancy and also significantly reduces the induction delivery interval, has fewer side effects and complications and also reduces the dose of Misoprostol. Hence, an attempt is made in the present study to assess the efficacy of combination of Mifepristone and Misoprostol versus single drug Misoprostol alone for induction of labor. Methods: A prospective comparative study of 50 cases in each study group, one under Misoprostol induction (group 1) and one under Mifepristone plus Misoprostol induction (group 2) were done and observations made in terms of improvement in Bishop’s score, induction-delivery interval and requirement of subsequent doses of Misoprostol. Results: 64% of the patients were observed with improved Bishop’s score. Induction delivery interval was shorter in the group 2 and noteworthy feature is 46% patients did not require even a single dose of Misoprostol after cervical ripening with Mifepristone suggesting that only Mifepristone may be only drug required in future for induction. Conclusions: Mifepristone with Misoprostol is efficient combination for induction of labour as compared to Misoprostol alone.